Analysis of Online Zakat Mechanism Reviewed from the Perspective of Maqashid Sharia (Case Study of BSI Maslahat Surabaya) - Teguh Eka Prasetya; Usamah Abdurrahman; Annisa Silviana Yuniar; Amiera Aulia Taftazani (PT. Padang Tekno Corp, 2026)
The development of digital technology has encouraged zakat management institutions, including BSI Maslahat, to provide online zakat services. This study aims to analyze the online zakat mechanism at BSI Maslahat Surabaya and review it based on the perspective of maqashid syariah. This study uses a qualitative method with a descriptive approach. Data was obtained through field research in the form of interviews with BSI Maslahat Surabaya and a literature study on the concept of maqashid syariah. The analysis focused on the suitability of the zakat collection and distribution mechanism with the five aspects of maqashid, namely hifz al-din, hifz al-nafs, hifz al-aql, hifz al-nasl, and hifz al-mal. The results of the study show that the online zakat mechanism at BSI Maslahat Surabaya is generally in line with the principles of maqashid syariah, in terms of ease of payment, distribution of funds to mustahik, transparency of information, empowerment programs, and the security system for fund management. However, improvements in digital literacy and optimization of information delivery are still needed.